2021
DOI: 10.7759/cureus.12966
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Hidradenitis Suppurativa: Case Report and Review of Literature

Abstract: Hidradenitis suppurativa is a chronic, recurrent follicular-based inflammatory condition classically occurring in apocrine-rich areas; commonly affected areas include the anogenital, axillary, inframammary, and inguinal regions. Infrequently, hidradenitis suppurativa can occur in locations where apocrine glands are scant or absent; in this setting, it has been referred to as ectopic hidradenitis suppurativa. The case of a 59-year-old man with ectopic hidradenitis suppurativa on his right posterior thigh is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…HS, like other inflammatory dermatoses, is associated with mental comorbidities, mainly Depression and Anxiety. Metaanalysis involving 28 studies related to Depression and HS, and 12 studies related to Anxiety, showed a prevalence of 21% (95% CI [17][18][19][20][21][22][23][24][25] in relation to Depression, and 12% (95% CI [6][7][8][9][10][11][12][13][14][15][16][17] in relation to Anxiety in patients with HS with wide variations in both cases, demonstrating that patients with HS have a high impact of Depression and Anxiety [196]. In a prospective study with 51 patients with HS, 29.4% presented mental symptoms, mainly symptoms of depressive disorder.…”
Section: Hidradenitis Suppurativa and Mental Health (Psychiatric Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…HS, like other inflammatory dermatoses, is associated with mental comorbidities, mainly Depression and Anxiety. Metaanalysis involving 28 studies related to Depression and HS, and 12 studies related to Anxiety, showed a prevalence of 21% (95% CI [17][18][19][20][21][22][23][24][25] in relation to Depression, and 12% (95% CI [6][7][8][9][10][11][12][13][14][15][16][17] in relation to Anxiety in patients with HS with wide variations in both cases, demonstrating that patients with HS have a high impact of Depression and Anxiety [196]. In a prospective study with 51 patients with HS, 29.4% presented mental symptoms, mainly symptoms of depressive disorder.…”
Section: Hidradenitis Suppurativa and Mental Health (Psychiatric Dise...mentioning
confidence: 99%
“…Clinically, it manifests as multiple papules, nodules and abscesses in flexural areas of the body such as armpits, inguinal and perigenital regions and perineum [4], as well as in non-flexural areas such as legs, dorsal and pectoral regions, ears and penis [5]. HS can also manifest in unusual locations such as the abdomen, amputation stump, cesarean scar, chest, dorsal region of the foot, eyelids, knees, post-auricular region and scalp [6]. There are reports of involvement of the follicular portion of the pilosebaceous units [7] and genetic predisposition [8], and associations with significant comorbidities such as smoking, obesity, metabolic syndrome and diabetes mellitus [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Gutierrez et al . [ 9 ] reported an ectopic HS that is located in a 59-year-old male’s right posterior thigh, whereas Rondags et al . reported it in a 28-year-old male’s right dorsal foot [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lesions most commonly arise in the anogenital, axillary, inframammary and inguinal regions. Seldom, these lesions occur in sites where apocrine glands are either absent or scanty 2 3…”
Section: Introductionmentioning
confidence: 99%
“…Unusual areas where the disease was reported as atypical are the abdomen, amputation stump, caesarian scar, chest, dorsal foot, eyelids, knees, retroauricular region and scalp 2 3…”
Section: Introductionmentioning
confidence: 99%